PEMANFAATAN KAOS JEMBERAN SEBAGAI CENDERAMATA DALAM MEMPERKENALKAN KEARIFAN LOKAL DAN PARIWISATA JEMBER - Siti Husnul Hotimah; Reiga Ritomiea Ariescy (UPT Penerbitan Universitas Jember)
Local wisdoms is part of the culture of a society that can not be separated from the language of the community itself. Local wisdoms is usually inherited from generation to generation through stories by word of mouth. Local wisdoms of an area can not be known away without telling anyone. Therefore, the government needs to introduce local wisdom of Jember region with a unique medium that can be embedded in the public mind or tourists. In this article the authors describe how the use of T-shirt as a souvenir Jemberan in introducing local wisdom Jember. Kaos Jemberan a shirt by pictures or words that represent the culture, customs or characteristic of Jember City. Kaos Jemberan through public and tourists can understand how the culture in Jember, how hallmark of Jember, Jember City uniqueness and various other things about the Jember City.